Classification of African Native Plant Foods Based on Their Processing Levels - Jideani, Afam I. O.; Onipe, Oluwatoyin O.; Ramashia, Shonisani E. (Frontiers in Nutrition, 2022)
With increasing advocacy for plant food consumption, the sub-Saharan Africa landscape is home to diverse plant-based food commodities. The need to leverage the advantages of unprocessed/minimally processed foods over ultra-processed foods (UPF) is a system that requires exploitation. Most of the crops produced in the continent are either classified as traditionally or moderately processed foods. However, the rise in industrialisation and formalisation of markets are impacting and marginalising traditional food processing. Current food processing classification frameworks was briefly discussed. The level of processing of cereals, grains, fruits, vegetables, roots, and tuber crops in the continent requires intervention from nutritionists, food scientists, scientific and governmental bodies to gain a holistic view and tackle the issue of food insecurity in Africa. This paper reviews the levels of processing of African foods, the challenges, and future directions.